(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Gestational diabetes mellitus affects approximately 14% of pregnancies globally, with maternal age above 30 years, pre-pregnancy BMI exceeding 27 kg/m², and family history constituting primary risk determinants. This investigation evaluated preventive interventions including dietary modification restricted to 1800-2000 kcal daily and moderate physical activity totaling 150 minutes weekly, demonstrating 31% reduction in GDM incidence among high-risk cohorts. Maternal complications decreased by 23%, while macrosomia rates declined from 18.4% to 11.7%, supporting early screening and lifestyle-based prevention protocols.